Decreased Transition Rate From Situational Insomnia to Chronic Insomnia by One-Week Internet Cognitive Behavioral Treatments for Insomnia During the COVID-19 Pandemic - Feng, Fei; Zhang, Chenxi; Liang, Hanwen; Xu, Guojian; Luo, Xian; Liu, Shuai; Xu, Yan; Yang, Lulu; Zhang, Li; Lin, Lianhong; Zhang, Bin (Frontiers in Psychiatry, 2022)
Purpose: The purpose of the study was to determine the long-term effects of one-week self-guided internet cognitive behavioral treatments for insomnia (CBTI) on situational insomnia during the COVID-19 pandemic. Patients and methods: The participants with situational insomnia (n = 194) were recruited from March 2020 to April 2020 in Guangzhou, China. The insomnia severity index (ISI), pre-sleep arousal scale (PSAS), and hospital anxiety and depression scale (HADS) were evaluated at baseline and a one-week internet CBTI program was delivered to all individuals. The participants were divided into the complete treatment group (the participants completed all 7 modules of the CBTI course, n = 75), and the incomplete treatment group (the participants completed 0 - 6 modules of the CBTI course, n = 119). A total of 135 participants completed the post-intervention assessments. At 3 months follow-up, a total of 117 participants (complete treatment group: n = 51; incomplete treatment group: n = 66) completed the assessments of the ISI, PSAS and HADS. The transition rate from situational insomnia to chronic insomnia (duration of insomnia ≥ 3 months and ISI ≥ 8) was calculated in the two groups. Linear mixed effect model was used to investigate the effect of group (between the two groups), time (baseline vs. follow-up), and interaction (group x time) on various questionnaire score. Results: The transition rate from situational insomnia to chronic insomnia was significantly lower in the complete treatment group compared to the incomplete treatment group (27.5%, 14/51 vs. 48.5%, 32/66, p = 0.023). There were significant differences in group effect (p = 0.032), time effect (p = 0.000) and group × time effect (p = 0.048) between the two groups in the ISI total score. The ISI total scores decreased in both groups during follow-up compared to their baseline values, with a greater magnitude of decrease in the complete treatment group. Conclusion: Our results suggested that one-week self-guided internet CBTI prevented the development of chronic insomnia from situational insomnia during the COVID-19 pandemic.